ANALISIS KONTEKS WACANA DALAM PIDATO MENDIKBUDRISTEK NADIEN MAKARIN PADA PERINGATAN HARDIKNAS 2024 - Dyah, Ayu (BASINDO : jurnal kajian bahasa, sastra Indonesia, dan pembelajarannya, 2024)
This study analyzes the influence of context in understanding speeches as significant discourse in public communication. Using a qualitative method with discourse analysis, it reveals that the topic, delivery medium, and participant background play crucial roles in shaping the meaning of speeches. Understanding signs and signifiers according to Saussure’s theory enriches discourse interpretation, reduces misunderstandings, and enhances communication effectiveness. The findings emphasize the importance of context analysis in comprehending speeches and how linguistic and non-linguistic elements work together.